Modern Healthcare Technologies: Legal and Ethical Concerns of Artificial Intelligence - Imam, Hasan; Hossain, Md Jubayar; Momotaj, FNU; Moniruzzaman , Mohammad (Information Technology and Science (ITScience), 2024)
AI implementation within the health care system has the ability to improve the quality of results, as well as the diagnostic operations, and productivity. That being said, incorporating the tools into the healthcare setting along with growth of its applications, the question of legal, ethical, and regulatory compliance arises. In this review article, therefore, the ethical issues, legal concerns, and the responsibilities that arise with the application of AI in healthcare with reference to concerns like privacy, bias of the algorithms, how transparent they are, and accountability, and weakened doctor-patient relationship have been reviewed. Legal areas of concern are mainly, liability, vast legal voids that exist, and intellectual property rights, legal frameworks that must be developed to redress these growing legal issues. From the article, the author underscores the concept of Innovation for AI and Responsibility for it; it therefore calls upon the regulatory authorities to come up with a strategic and systematic approach to AI, encourage AI to declare their stands as well as develop ways of war against bias via diversity of data. Moreover, roles and responsibilities in case of harm, a patient-centered approach to using AI, as well as ongoing surveillance of AI systems are discussed. These measures are in a bid to guarantee that the adoption of AI in health care is right, efficient and safe to reduce the negative impact while improving the patients’ lot. Pointing to the need for proactive governmental regulation, cooperative work of all the interested stakeholders, and emphasizing patient safety as a key foundation for the effective deployment of the analyzed AI applications in the sphere of healthcare, the conclusion returns to the idea that AI has to be presented as a tool for beneficial changes in the existing system of healthcare delivery that has to be used in accordance with the main ethical and legal guidelines.